Why do emerging economies borrow short term? - Broner, Fernando, 1970- 1970- (Policy research working paper, 2004)
"Broner, Lorenzoni, and Schmukler argue that emerging economies borrow short term due to the high risk premium charged by international capital markets on long-term debt. They first present a model where the debt maturity structure is the outcome of a risk-sharing problem between the government and bondholders. By issuing long-term debt, the government lowers the probability of a liquidity crisis, transferring risk to bondholders. In equilibrium, this risk is reflected in a higher risk premium and borrowing cost. Therefore, the government faces a tradeoff between safer long-term borrowing and cheaper short-term debt. Second, the authors construct a new database of sovereign bond prices and issuance. They show that emerging economies pay a positive term premium (a higher risk premium on long-term bonds than on short-term bonds). During crises, the term premium increases, with issuance shifting toward shorter maturities. This suggests that changes in bondholders' risk aversion are important to understand emerging market crises. This paper--a product of the Investment Climate Team, Development Research Group--is part of a larger effort in the group to understand financial markets in emerging economies"--World Bank web site